Popularizing mushroom to masses - Dutt, Som (Indian Horticulture, 2019)
The ICAR-Directorate of Mushroom Research, Solan, organized a Mushroom Awareness Campaign on 21 February 2018 at Vegetable Science Division, Indian Agricultural Research Institute, Pusa, New Delhi. Its objective was to create awareness about benefits of mushrooms, methods of cooking and products of mushrooms amongst all stakeholders. The event was attended by various stake-holders. The participants from the Rajendra Central Agricultural University, Samastipur; Indian Institute of Horticultural Research, Bengaluru; NHRDF, New Delhi; HAIC, Murthal; M/s Saumya Foods, Dehra Dun; Mrs Manorama Singh from Bihar and Elle Mushroom, Karnal, exhibited their mushrooms products, dry oyster, button mushrooms, cordyceps, mushroom pickles, biscuits, noodles, corn exudates, instant soup powder, mushroom preserve, mushroom chips, mushroom ketchup, mushroom nuggets, ready-to-cook mushroom tikki, mushroom candy, mushroom jam, cakes, mushroom bhujia, mushroom laddoo and mushroom gulabjamun. Various live specimens of different mushrooms such as kabul dhingri, yellow, pink, blue, white and gray oyster, button, rishi, cordycepsmilitaris, monkey head mushroom, etc. were also displayed.